Verbreitung des Makrozoobenthos in der Mecklenburger Bucht (sügliche Ostsee) - rezent und im historischen Vergleich ... - Zettler, Michael L.; Bönsch, Regine; Gosselck, Fritz (Leibniz-Institut für Ostseeforschung Warnemünde, 2000)
Meereswissenschaftliche Berichte No 42 2000 - Marine Science Reports No 42 2000 ... : This study aims at to give an overview of the macrozoobenthos of the Mecklenburg Bight (Western Baltic Sea) with emphasis on water depths between 5 and 29.5 meters. The data result from several research cruises in 1999. Such an extensive investigation of macrozoobenthos within one year was performed for the first time. The study is focused on biology and recent distribution of the macrozoobenthos. Therefore, population dynamics of species and their variability in time and space are only included for some dominant species in order to follow their long term development. Particularly for long living bivalves (Arctica islandica and Astarte borealis) morphological and population characteristics were recorded. In addition, some other dominant species such as the polychaete worm Scoloplos armiger and the crustacean Diastylis rathkei are discussed in more detail. Moreover, a list of the taxa is presented using all data on macrozoobenthos available for the inner and outer coastal waters of the Mecklenburg Bight since ...